The effect of Ochratoxin A on antimicrobial polypeptide expression and resistance to water mold infection in channel catfish (Ictalurus punctatus). (October 2016) - Zahran, Eman; Manning, Bruce; Seo, Jung-Kil; Noga, Edward J.
Abstract: Mycotoxin contamination of agricultural commodities poses a serious risk to animal health, including aquaculture species. Ochratoxin A (OA) is the most immunotoxic ochratoxin, yet little is known about its effect on immune function in fish. Antimicrobial polypeptides (AMPPs) are one of the most potent, innate, host defense factors, yet very little is known about what types of chronic stressors affect their expression. Among the most prevalent and potent AMPPs in fish are histone-like proteins (HLPs). In this study, fish were fed 2, 4, or 8 mg OA/kg diet. Skin antibacterial activity and HLP-1 levels were measured on Days 0, 28 and 56. Feeding 2, 4 or 8 mg OA/kg diet resulted in significant growth depression, but higher levels (4 or 8 mg OA/kg diet) resulted in lowering feed intake (FI) and impaired feed conversion ratio. In addition, feeding 8 mg OA/kg diet increased susceptibility to experimental water mold ( Saprolegnia ) challenge, suggesting that OA toxicity might contribute to some saprolegnosis outbreaks. However, there were no changes in AMPP expression in any treatment group. Our data suggests that the increased disease susceptibility of channel catfish due to OA is probably due to mechanisms other than a direct effect on antimicrobial polypeptide expression. Highlights: Feeding Ochratoxin A (OA) at 2, 4 or 8 mg OA/kg diet led to growth depression in channel catfish. Feeding higher levels of 4 or 8 mg OA/kg diet resulted in lowering FI and impaired FCR. No changes in AMPP expression observed in skin extracts of channel catfish fed 0 or 8 mg OA/kg diet. Feeding higher level of 8 mg OA/kg diet increased susceptibility to water mold ( Saprolegnia ) challenge.